Ultrawideband Circularly Polarized Cavity-Integrated EBG-Backed Archimedean Spiral Antenna for IoT Applications - Bancha Luadang; Pisit Janpangngern; Cong Li (My University, 2025)
This paper presents a compact ultrawideband circularly polarized Archimedean spiral antenna integrating a cavity-backed structure with a circular EBG reflector. The hybrid design enhances gain, suppresses backward radiation, and improves directivity, particularly below 3.0 GHz. The antenna covers 1.5–9.0 GHz with |S11| ≤ –10 dB and axial ratio ≤ 3 dB. Simulations show peak gain over 11.96 dBic at 6.5 GHz and a front-to-back ratio improvement due to the cavity. The proposed structure is well-suited for GPS, Wi-Fi, and IoT applications.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Microwave Engineering and Waveguides